Influence of blockchain technology in manufacturing supply chain and logistics - Abirami Raja Santhi; Padmakumar Muthuswamy (Logistics, 2022)
Background: Blockchain is a digitally managed, distributed, and decentralized ledger used to record transactions in an immutable format. Its characteristics in providing trust, transparency, and traceability make it attractive for applications where transactions are involved. Originally intended to support financial transactions, the technology has gained attention even in non-financial sectors such as health care, manufacturing, retail, and government services. Methods: For centuries, the various functions of manufacturing industries have worked based on the relationship and trust that they have with their upstream and downstream stakeholders. In addition, as the conventional factories are growing into giant gigafactories, the participation of several intermediaries further complicates the supply chain and logistics operations. Hence, the article aims to provide a comprehensive overview of the role of blockchain technology in addressing supply chain and logistics-related challenges by analyzing, organizing, and reviewing the literature. Results: The study shows that blockchain technology can transform the supply chain and logistics into secure, agile, trusted, and transparent functions. A conceptualized application scenario demonstrates the benefits of blockchain technology in providing provenance and traceability to critical products. Conclusions: In particular, a private or permissioned blockchain is suitable for multi-organizational businesses such as supply chain and logistics. In addition, IoT-blockchain integration, smart contracts, and asset tracking has immense benefits in the future.
Keywords: 650; Industry 4.0; blockchain; asset tracking; consensus mechanism; cryptography; cyber security; distributed ledger; Industry 5.0; manufacturing supply chain; smart contracts